Motivasi Berprestasi Dalam Upaya Membangun Karakter Unggul Melalui Literasi Digital Pada Orang Tua Terhadap Pola Asuh Anak di Cirebon dan Indramayu - Rr. Sri Wachyuni; Tri Sulistyaningtyas; Shinta Yuniarti; Fadila Nisa Ul Hasanah (Universitas Lancang Kuning, 2022)
The impact of the Covid-19 pandemic on the education sector is significant, especially in teaching and learning activities which have been forced to change from offline methods at school to online methods from home. This sudden transition has made many parents unprepared with their main responsibilities and duties as educators, thus affecting children's learning activities at home to be less effective. This activity aimed to determine the extent of achievement motivation possessed by parents in building their superior character as an effort to optimize the role of online learning mentoring. Data collection techniques using observation, interviews, and questionnaires. The training and digital learning modules provided are one of the interventions to increase the insight of parents, especially changing their thinking paradigm as an adaptation to online learning so that they are able to maximize their role when accompanying children to study at home. The results showed that after being given training and digital learning modules, some of the participants became more open-minded and more prepared to become partners with children studying at home. This change also occurred because of the great involvement of the participant coordinator as a support system in helping to monitor, control, and motivate participants on a regular basis in their area. Considering the limited characteristics of the participants, the presence of supporting staff who are ready to assist directly in the field becomes one of the reinforcements for achieving a change, namely adding insight.